SCREENING FOR IODINE DEFICIENCY – MORE THAN A MEDICAL APPROACH - Vulpoi, Carmen; Ungureanu, Maria-Christina; Azoicai, Doina; Vulpoi-Naghel, Iuliana; Anton, Mihaela Cristina; Preda, Cristina (European Scientific Journal, ESJ, 2014)
Working as a team began more and more important in many fields, including medicine. After an era of fragmentation, when the need of deepen the knowledge led to supra-specialization, we witness now the reassembly of these distinct parts, in order to obtain a comprehensive view. This is true not only for research, but also for the clinical practice. We present the building of a team who started with a screening and continued with other evaluations in a city from the eastern part of Romania. The goal of the study was to evaluate the iodine status in a former iodine deficient area. Two parameters were necessary, evaluation of thyroid volume and urinary iodine in a representative group of children. The initial pure endocrinological team increased by adopting new members: medical (nurses, epidemiologist, biochemist) and non-medical (schoolteachers). The results induced new studies and the team had growth and proved the utility of interdisciplinarity.